Master of flood preparedness (MOFP): Game-based learning to prepare youth to be aware, prepared, and resilient in facing floods - Mohd Rozaimy, Ridzuan; Jamal Rizal, Razali; Ju, Soon-Yew; Kong, Lai-Kuan; Amirudin, Mohd Zani; Noor Amira Syazwani, Abd Rahman (Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2023)
Frequent occurrences of floods in Malaysia lead to loss of life and property damage. Among the vulnerable groups to these disasters, the youth stand out due to socio-economic factors like their age, financial instability, and limited experience. In the context of disaster risk reduction, prioritizing flood preparedness emerges as a critical component to mitigate the impact of flood disasters on both the nation and its citizens. In the context of flood preparedness, accessibility to materials for flood is still in deficit and a future-ready learning approach is required. To address this need, the Master of Flood Preparedness (MOFP) was created to increase awareness of flood preparedness among young individuals. This gamebased learning approach encompasses three key components: flood preparedness-related e-books, a game board, and play cards. These elements are integrated into a game format to deliver and enhance youth awareness of flood preparedness. This exceptional MOFP stands out due to its innovative fusion of three elements in one product. It effectively leverages the advantages of online-oriented resources, such as e-books, QR codes, e-journal articles, and e- newspaper articles, while also incorporating traditional offline components like board games and playing cards. Emphasizing a learn-while-playing approach, this platform enables users, especially the youth, to enhance their awareness of the importance and necessity of flood preparedness. This productcan also help the country to achieve Sustainable Development Goals (SDGs).